Legal Protection for Children in Cases of Domestic Violence in the Indonesian Households - Alifiyah, Rifdah; Anshori, Isa (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
This study aims to investigate and evaluate the many legal protections available to children who experience domestic abuse. Additionally, it seeks to provide a comprehensive framework for enhancing legal protection measures specifically designed for child victims of domestic violence. This study employs a normative approach to analyze legal issues by examining legislation. The material examined pertains to legal statutes and laws concerning instances of familial child abuse. This study establishes that child domestic violence can manifest in various forms, including physical, sexual, emotional, neglect, and economic abuse. The act of violence infringes upon the rights of children and adversely affects their overall welfare, leading to diminished cognitive abilities, impaired emotional regulation, challenges in social interaction, psychological developmental disorders, difficulties in establishing relationships and trust, increased susceptibility to depression and anxiety disorders, and various mental health issues. The legal safeguarding of children in Indonesia is governed by Law No. 23/2002 on Child Protection, which was subsequently revised by Law No. 35/2014. This legislation serves as the legal foundation for the protection of children, including all endeavors aimed at ensuring their safety, well being, and the fulfillment of their rights to thrive, mature, progress, and engage fully.